Wrist Fusion through Centralisation of the Ulna for Recurrent Giant Cell Tumour of the Distal Radius - Dinesh Kumar Meena; Srikiran Thalanki; Shiv Bhagwan Sharma (Journal of Orthopaedic Surgery, 2016)
Purpose. To review the outcome of wide resection and wrist fusion through centralisation of the ulna for recurrent giant cell tumour (GCT) of the distal radius in 10 patients. Methods. Records of 7 women and 3 men aged 25 to 40 years who underwent wide resection and wrist fusion through centralisation of the ulna for grade I (n=6) and grade II (n=4) recurrent GCT of the distal radius were reviewed. Functional outcome was evaluated using the modified Musculoskeletal Tumor Society scoring system. Grip strength and range of motion of the metacarpophalangeal joint were also assessed. Results. The mean follow-up period was 45 (range, 30–60) months. All tumours were benign and there was no evidence of metastasis. The mean grip strength was 45% (range, 30–70%) of the contralateral side. All patients achieved normal range of motion of the metacarpophalangeal and interphalangeal joints, but 4 patients had an extensor lag of the thumb. The mean time to wrist fusion was 6 (range, 4–8) months: 3 to 4 months for the 6 patients with bone grafting and 5 to 6 months for the 4 patients without bone grafting who developed painful subluxation necessitating total wrist arthrodesis using a plate and morcellised bone grafts. Conclusion. Wrist fusion through centralisation of the ulna for recurrent GCT of the distal radius is a viable option, despite a loss of wrist motion.